Kompetensi Profesional Guru Bimbingan Konseling Dalam Pemecahan Masalah Belajar Siswa di SMP Negeri 20 Batanghari - Amirah, Nadiratul; Y, Yarmis; T, Taufik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Learning problems experienced by students are complex issues that have a direct impact on academic success. In this case, the role of the BK teacher is very important to help students overcome various learning problems, both those originating from internal and external factors. This study aims to describe the professional competence of BK teachers when handling student learning problems at SMP Negeri 20 Batanghari. This study uses a qualitative descriptive approach, with data collected through observation and interviews with BK teachers. The results of the study revealed that BK teachers who have a high level of professional competence or identify sources of learning problems appropriately, provide individual and group counseling services effectively, and establish effective cooperation with schools and parents. These findings indicate that the professional competence of BK teachers has an important role in the success of handling learning problems faced by students.